The Effect of Midwife's Knowledge on Breast Milk Production for Mothers in Childbirth - Iis wahyuni (Institute of Computer Science (IOCS), 2022)
Breast milk (ASI) is a liquid secreted by the mother's breast glands in the form of natural foods or the best nutritious and high-energy milk produced during pregnancy. Breast milk is the perfect and best food for babies, especially babies 0-6 months because it contains the nutritional elements needed for optimal baby growth and development. This research is a type of qualitative research, using descriptive method. The definition of qualitative research can be understood as a research procedure that seeks to understand and interpret the meaning of an event of human behavior interaction in certain situations according to the researcher's own perspective. and the results of this study explain that, breastfeeding is a natural process and is an art that must be re-studied, because breastfeeding actually not only provides an opportunity for babies to grow into physically healthy human beings but is also able to increase intelligence and have emotional stability, positive spiritual development and better social development. In addition to the mother's knowledge factor, another factor that affects exclusive breastfeeding is the role of health workers. The role of health workers is to provide health education by providing counseling to provide encouragement to mothers by providing information about the smooth running of milk, especially the effect of social support on the smooth production of breast milk, then providing knowledge by direct education to patients, distributing leaflets and posters to the public, and involving families to provide support to breastfeeding mothers to always give exclusive breastfeeding from birth to 6 months of age, because the presence of professional health workers can be a supporting factor for mothers in determining the sustainability of breastfeeding now and in the future.